RATIONAL RESTRICTIONS OR PRUNING OF RIGHTS ? DEADLINE FOR SUBMITTING FORMAL TESTS AT THE CONSTITUTIONAL COURT - Pratama, Agung Barok; Imaduddin, Aufi; Yusron Rofi'i, Hilmi; Leo Saputra, Aldila; Agung Barok Pratama; Aufi Imaduddin; Hilmi Yusron Rofi'I; Aldila Leo Saputra (Universitas Islam Negeri Raden Intan Lampung, 2024)
The time limit in the judicial review of legislative process was first made in Constitutional Court Decision Number 27/PUU-VII/2009, in legal considerations the judge made a new law (judge making of law) by limiting the filing of formal test applications 45 today the law was published in the state gazette. This was done for the sake of legal certainty and the impact of the formal test application submitted past the 45-day deadline would be rejected by the Constitutional Court. This research uses a normative or doctrinal juridical type that focuses on library research. The purpose of this research is to find out the legal reasoning of the Constitutional Court judges in limiting the filing of formal tests and analyzing these restrictions from the aspect of justice. This research is a doctrinal research using statutory, conceptual and case approaches. The results of the study show that restrictions on the filing of formal tests are imposed in order to achieve legal certainty, so that the law requested for a formal test is more quickly known whether its status has been made legally or not, because formal testing will cause the law to be canceled from the start. Time restrictions in the Constitutional Court are not entirely contrary to the principle of justice, because in practice the Constitutional Court still provides space of justice for applicants to submit formal tests.